2017
DOI: 10.1016/j.matchemphys.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Annealing to achieve lower resistivity in Ga-doped ZnO epitaxial films grown from low-temperature aqueous solution

Abstract: Various annealing conditions were examined for enhancing the electrical conductivity of galliumdoped ZnO (ZnO:Ga) epitaxial films grown from a low-temperature aqueous solution. The resistivity of the films decreased with increasing annealing temperature, accompanying increases in both the carrier concentration and mobility. However, the improvement obtained from 0.5 h of annealing was limited because the films spalled when the temperature exceeded ~300 °C. The temperature at which spalling of the films occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has been reported that ZnO crystals grown from aqueous solutions contain a small amount of hydroxide ions as impurities, which can reduce the mobility of electrons in the crystal. 26,31) The amount of hydroxide ions incorporated in ZnO during the crystal growth is expected to depend on the pH of the reaction solution.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…It has been reported that ZnO crystals grown from aqueous solutions contain a small amount of hydroxide ions as impurities, which can reduce the mobility of electrons in the crystal. 26,31) The amount of hydroxide ions incorporated in ZnO during the crystal growth is expected to depend on the pH of the reaction solution.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…The ionic radii of Ga (0.062 nm) and Zn (0.074 nm) and covalent bond length of Ga-O (1.92 Å) and Zn-O (1.97 Å) are similar, resulting in low deformation of the ZnO lattice even at a high doping concentration [7,[22][23][24]. GZO thin films have been fabricated successfully through several deposition technologies such as molecular beam epitaxy (MBE) [25,26], pulsed laser deposition (PLD) [27,28], metal-organic chemical vapor deposition (MOCVD) [29], atomic layer deposition (ALD) [22], sputtering [30,31], thermal oxidation [32], aqueous solution deposition [33], and the sol-gel method [34]. PLD and MBE grown-GZO thin films exhibit excellent crystalline structures and low resistivity; nevertheless, scaling them up to standard industrial substrate sizes is difficult [22].…”
Section: Introductionmentioning
confidence: 99%